Constructing Inference-Proof Belief Mediators - Biskup, Joachim; Tadros, Cornelia (Data and Applications Security and Privacy XXIX, 2015)
An information owner might interact with cooperation partners regarding its belief, which is derived from a collection of heterogeneous data sources and can be changed according to perceptions of the partners’ actions. While interacting, the information owner willingly shares some information with a cooperation partner but also might want to keep selected pieces of information confidential. This requirement should even be satisfied if the partner as an intelligent and only semi-honest attacker attempts to infer hidden information from accessible data, also employing background knowledge. For this problem of inference control, we outline and discuss a solution by means of a sophisticated mediator agent. Based on forming an integrated belief from the underlying data sources, the design adapts and combines known approaches to language-based information flow control and controlled interaction execution for logic-based information systems.